Topical application of snail mucin gel enhances the number of osteoblasts in periodontitis rat model - H. Hendrawati; Hanindya Noor Agustha; Rezmelia Sari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: Repair of bone damage represents a fundamental issue in the treatment of periodontitis. The important indicator employed to monitor the bone damage repair process is the number of osteoblast cells. Achatina Fulica snail mucin (SM) contains glycosaminoglycans which have the potential to increase their number. However, the use of SM in dentistry remains limited. Purpose: To determine and prove the effect of SM gel in increasing the number of osteoblasts in rat models suffering from periodontitis. Methods: This study used 36 rat models divided into three groups, namely; a treatment group (T: 20% snail mucin gel, n = 12), a positive-control group (P: hyaluronic acid gel, n = 12) and a negative-control group (N: CMC-Na gel, n = 12). 0.2 ml of all material was applied to a pocket by means of a tuberculin syringe once a day for 14 days. Histologic observations using Haematoxylin-Eosin staining were carried out on days 3, 5, 7 and 14. Data was analyzed by two-way ANOVA followed by a post-hoc LSD. Results: A significant difference existed between the number of osteoblasts in the test groups. The highest number of osteoblasts observed was consistently that in the treatment group. Conclusion: The application of 20% snail mucin gel was effective in enhancing the number of osteoblasts in rats suffering from periodontitis.